Violation of PT Universal Pharmaceutical's Business Law - Aprinawati; Ariko Syahputra Silaen; Diki Maulana; O Marito Sinurat; Wilson Ambarita; Zayan Noval Ataya Ginting (PT FORMOSA CENDEKIA GLOBAL, 2023)
PT Universal Pharmaceutical is a pharmaceutical company involved in a serious business law violation case. In an effort to avoid violating business laws, their internal policies and business practices. Companies also need to increase their transparency and accountability to the public in the future, PT Universal Pharmaceutical needs to make changes in the management and authorities. PT Universal Pharmaceutical's business law violation case serves as a warning to other companies to pay close attention to their business practices and comply with applicable laws, in order to build a good and sustainable reputation in the long term.